Augmented Reality (AR) media-aided literature learning tool for elementary school students - Seni Apriliya; Weni Nuraeni; Yeyen Nurjanah; Muhammad Feri (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2023)
Learning devices need to be designed according to the characteristics of the material and be innovative. The results of the field study show that learning the subject of Indonesian fairy tale messages in elementary schools has not been fully implemented using such media, teaching materials, and assessment tools. Referring to this, this study aims to develop a literary learning device assisted by Augmented Reality (AR) media. This development research refers to the design-based research (DBR) development model from Amiel and Reeves (2008). The subjects of this development research trial were twenty students and a third-grade elementary school teacher. Data collection techniques used are semi-structured interviews, observation, and documentation. Data analysis is done by reducing, and presenting, until finding the interpretation of the data. The results of the study in the form of learning device products consisting of learning media, teaching materials, and assessment instruments showed that the Augmented Reality media-assisted literary learning device was validated as very feasible (85percent) with a high level of practicality category (93percent). The implication is that this product can be used in learning literature in elementary schools as an innovative alternative learning tool.Keywords: learning tools; teaching materials media; assessment; Augmented Reality (AR)Perangkat pembelajaran sastra berbantu media Augmented Reality (AR) untuk peserta didik SDPerangkat pembelajaran perlu dirancang sesuai karakteristik materi dan inovatif. Hasil studi lapangan menunjukkan pembelajaran dengan pokok bahasan pesan dongeng bahasa Indonesia di SD belum sepenuhnya dilaksanakan menggunakan media, bahan ajar, dan alat penilaian. Mengacu pada hal tersebut, penelitian ini bertujuan untuk mengembangkan perangkat pembelajaran sastra berbantu media Augmented Reality (AR). Penelitian pengembangan ini mengacu pada model pengembangan design-based research (DBR) dari Amiel dan Reeves (2008). Subjek uji coba penelitian pengembangan ini adalah dua puluh orang siswa dan seorang guru kelas tiga SD. Teknik pengumpulan data yang digunakan yaitu wawancara semi terstruktur, observasi dan dokumentasi. Analisis data dilakukan dengan cara mereduksi, menyajikan, sampai menemukan interpretasi data. Hasil penelitian berupa produk perangkat pembelajaran terdiri atas media pembelajaran, bahan ajar, dan instrumen penilaian yang menunjukkan bahwa perangkat pembelajaran sastra berbantu media Augmented Reality tersebut tervalidasi sangat layak (85persen) dengan kategori tingkat kepraktisan tinggi (93persen). Implikasinya, produk ini dapat digunakan pada pembelajaran sastra di SD sebagai perangkat pembelajaran alternatif yang inovatif.Kata kunci: perangkat pembelajaran; bahan ajar; media; penilaian; Augmented Reality (AR)